2012
DOI: 10.1016/j.jjcc.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

P-wave parameters and cardiac repolarization indices: Does menopausal status matter?

Abstract: Tpeak to Tend interval decreased significantly while QT intervals and P-wave parameters did not change in postmenopausal women when compared to premenopausal women. Association of these findings with changes in levels of sex steroids and their prognostic implications need to be elucidated with further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…A study by Siniscalchi et al1) investigated the effects of surgical early menopause on cardiac arrhythmia and demonstrated that surgical menopause and estrogen replacement therapy did not significantly affect atrioventricular transmission and ventricular repolarization time in women. In a study by Dogan et al13) Tp-e interval was significantly reduced while QT intervals and P-wave parameters were not altered in postmenopausal women compared to premenopausal women.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A study by Siniscalchi et al1) investigated the effects of surgical early menopause on cardiac arrhythmia and demonstrated that surgical menopause and estrogen replacement therapy did not significantly affect atrioventricular transmission and ventricular repolarization time in women. In a study by Dogan et al13) Tp-e interval was significantly reduced while QT intervals and P-wave parameters were not altered in postmenopausal women compared to premenopausal women.…”
Section: Discussionmentioning
confidence: 89%
“…While women are somewhat protected against atherosclerosis during their reproductive years, this can change after the onset of menopause 13). The rate of progression of atherosclerosis increases throughout the menopausal transition, and often asymptomatic cardiovascular changes occur during the postmenopausal stage 3)13). Many pathophysiological processes are affected in atherosclerotic diseases, including changes in the LA, that contribute to the development of AF.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Nakagawa et al 38 reported that Q-T interval is affected by natural events such as menopause, and probably these variations are in parallel to changes in serum levels of sex hormones, such as estrogen. 39 The exact impact of hormones, especially sex hormones, on arrhythmic mechanisms and cardiac conduction system are unclear. 39 Recently, the results of studies have shown that increased reactive oxygen species (ROS) due to elevated oxidative stress levels increase the cardiac inflammatory indices such as C-reactive protein (CRP) and the increase in age-related apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…39 The exact impact of hormones, especially sex hormones, on arrhythmic mechanisms and cardiac conduction system are unclear. 39 Recently, the results of studies have shown that increased reactive oxygen species (ROS) due to elevated oxidative stress levels increase the cardiac inflammatory indices such as C-reactive protein (CRP) and the increase in age-related apoptosis. 40 Consequently, it is possible that atrial negative regulation leads to a pre-excitation syndrome or a block in the AV node in post-menopause period.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiovascular system also suffers from structural or functional impairment [13]. Several studies showed that estrogen deficiency increased cardiovascular risk factors and subsequently increased cardiovascular morbidity and mortality [4, 5], and myocardial injury can take place in asymptomatic women in postmenopause [6, 7].…”
Section: Introductionmentioning
confidence: 99%